A Person's Image as a Personality Value - (:unkn) unknown (ISTANBUL UNIV, FAC LAW, 2021)
A person's image is a form that reflects his external appearance in a way that allows him to be recognized. Its strong connection to the person and his/her personality necessitates a legal assurance of one's image. Therefore, legal systems have acknowledged the existence of a right to one's image. As the existence of such a right is accepted, the definition of the term image becomes essential. The subject of the right to one's image is the image. Since the image is the subject of the right, the limit of the concept of one's image should be well drawn. The meaning attached to it in legal language differs from its meaning in daily language. Therefore, in order to clearly understand the term image, as a subject of a right and its connotations as a legal concept, it is important to establish a legal definition and analyze the elements constituting this definition.
Keywords: Right to a person's image; A person's image; Personality; Personality right; Right to the protection of one's image